The Effect Of E-Service Quality And E-Trust On Customer Satisfaction In PLN Mobile Application Users In The Rajapolah Customer Service Unit Area - Lulu, Neng; Sutrisna, Arga; Patimah, Titin (Universitas Dehasen Bengkulu, 2024)
The aim of this research is to determine the effect of e-service quality and e-trust on customer satisfaction among PLN mobile application users in the ULP Rajapolah area. The type of research used is quantitative research, with a sampling technique, namely non-probability sampling, with a total of 100 respondents. The data collection method in this research is a survey method using a questionnaire distributed to respondents online via google form. The data analysis technique in this research uses multiple linear regression analysis which is processed using SPSS 25. The results of this research show that the e-service quality variable has a positive and significant effect on customer satisfaction, the e-trust variable also has a positive and significant effect on customer satisfaction. Simultaneously, e-service quality and e-trust have a positive and significant effect on customer satisfaction of PLN Mobile application users in the ULP Rajapolah area.